Georgia Architectural and Historic Properties Survey of 512 Third Ave., Valdosta, Ga., 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
VA-47-F01-05: 508 Third Ave., Valdosta, Ga. One story shotgun with multi-gabled roof, exposed rafters. Porch closed in and modernized. Double hung sash windows with 6/6 lights set on brick piers. Fair condition. App. 1900-1910. Typical shotgun - however, this house has been severely altered, which makes it insignificant.
1 electronic record. 2 page scans [JP2]. 1 image scans [JP2, JPG]. 1 PDF/A files. 5 files. 39.3 MB (41,243,731 bytes).
Keywords: Lowndes County (Ga.); Valdosta (Ga.); Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.)